House dust mite sublingual allergen immunotherapy tablet is safe and well-tolerated in Dutch clinical practice - Tempels-Pavlica, Žana; Aarts, Mark C. J.; Welsing, Paco M. J.; van der Meer, Akke-Nynke; van der Zwan, Leonard P.; Uss, Elena; Knulst, André C. (Frontiers in Allergy, 2024)
Background: Half (49%) of clinically diagnosed allergic rhinitis (AR) patients are sensitized to house dust mite (HDM). If allergen avoidance and symptomatic medication fail, allergen immunotherapy may be indicated. Objective: We investigated safety and tolerability of HDM-sublingual immunotherapy by HDM-SLIT tablets in Dutch daily clinical practice. Methods: Daily intake of 12 SQ-HDM SLIT-tablet was investigated in a prospective, multicenter, observational study (EUPAS43753). It comprised 4 consultations in 1 year. Data on safety, tolerability, treatment satisfaction, symptomatic medication, compliance, and clinical effectiveness (Control of Allergic Rhinitis and Asthma Test; CARAT) were collected. Descriptive and longitudinal regression data analysis were performed. Results: Adult patients (n=415), mean (SD) age 36.6 (12.2) years, 61.4% female and 36% asthmatic were included. The preponderance (65.1%) experienced adverse events (AEs). These, mostly mild (67%), AEs comprised: oral allergic reactions (58.6%), respiratory (12.4%) and gastrointestinal symptoms (9.4%). Sixty (14.5%) patients stopped due to AEs and 76 (18.3%) for non-AE reasons. CARAT scores improved clinically significant by 6 points and symptomatic medication use decreased from 96.1% to 77.4%. Most patients (74.5%) tolerated the treatment and were compliant (>86.5%). The majority of patients (62.4 %) and investigators (69.4%) were satisfied with treatment. Conclusions: HDM SLIT-tablet is a safe and well-tolerated AR treatment. AEs occur often but are mostly mild and decreasing during the first year. CARAT scores improved and symptomatic medication use decreased suggesting better control of AR with treatment. Compliance, tolerability, and treatment satisfaction are good. However, patient follow-up and compliance remain important points of attention when initiating treatment.